Endouterine hemostatic square suture vs. Bakri balloon tamponade for intractable hemorrhage due to complete placenta previa - Kavak, Salih Burcin; Atilgan, Remzi; Demirel, Ismail; Celik, Ebru; Ilhan, Rasit; Sapmaz, Ekrem (Walter de Gruyter Gmbh, 2013)
Aim: To compare the efficiency of endouterine hemostatic square suture and the Bakri balloon tamponade in the treatment of bleeding due to complete placenta previa (CPP). Methods: Thirteen patients with the diagnosis of CPP and intractable bleeding were randomly divided into two groups in a single blind study. Group 1 (n=6) included patients in whom endouterine hemostatic square suture was applied, while group 2 (n=7) included patients in whom Bakri balloon tamponade was applied. The two groups were compared according to the maternal outcomes, the duration of caesarean section, the preoperative and the postoperative hemoglobin and hematocrit (Htc) values, the intraoperative and postoperative blood loss, as well as the newborn characteristics. Results: The duration of operation and the amount of intraoperative bleeding were significantly higher in group 1 (time: 78.3+/-8.1 vs. 62.8+/-3.9 min; P<0.05; intraoperative bleeding: 1946+/-242 vs. 1520+/-92 mL; P<0.05). The postoperative 24th h Htc values were found to be significantly lower in group 1 than in group 2 (25.6+/-3.7 vs. 29.5+/-1.3 g/dL; P<0.05). The postoperative blood loss was higher in group 1 than in group 2. (351+/-70 vs. 120+/-56 mL; P<0.05). Conclusion: There are two methods that are effective in preventing bleeding in CPP. However, the Bakri balloon tamponade may be a better alternative due to a shorter operation time and less blood loss.
Keywords: Bakri balloon tamponade; complete placenta previa; endouterine hemostatic square suture